663 Utilisation of children's emergency care services during epidemics and pandemics: a systematic review. (17th August 2022) - Roland, Damian; Gardiner, Adam; Razzaq, Darakhshan; Rose, Katy; Bressan, Silvia; Honeyford, Katy; Buonsenso, Danilo; Dalt, Liviana; De, Tisham; Farrugia, Ruth; Parri, Niccolo; Oostenbrink, Rianne; et al.
Abstract : Aims: Paediatric emergency departments (PED) around the world have reported a large decrease in the utilisation of emergency care services amongst children during the COVID-19 pandemic. This phenomenon has been observed during previous epidemics but the extent, trends or causes are not clear. The aim of the study was To assess the impact of epidemics and pandemics on the utilisation of paediatric emergency care services to provide health policy advice. Methods: Searches were conducted of Medline, EMBASE, CINAHL, Scopus, Web of Science, and the Cochrane Library for studies (until 8 th April 2021) that reported on changes in paediatric emergency care utilisation during epidemics. Two reviewers independently screened the results for inclusion. Data including study characteristics, PED visit data and other study findings were extracted. Quality assessment was completed using the National Institute for Health (NIH) quality assessment tool. Results: 131 articles were included within this review, 80% of which assessed the impact of COVID-19. Studies analysing COVID-19, SARS, MERS and Ebola found a reduction in PED visits whereas studies reporting on H1N1, Chikungunya Virus and an E coli outbreaks found an increase in PED visits. For COVID-19 there was a reduction of 63.86% (95% confidence interval 60.40% - 67.31%) with a range of -16.5% to -89.4%. Synthesis of results suggests that the fear of the epidemic disease, from either contracting it or its potential adverse clinical outcomes, resulted in reductions and increases in PED utilisation, respectively. A world map showing the distribution by country including all the articles can be found in figure 1 . It highlights the USA (n = 41), Italy (n = 25) and the UK (n = 9) as major publication countries whilst also showing the global spread of included articles. Using the World Bank Classification of Countries shows that the majority of the included articles analysed the effect in 'Higher Income' countries (n = 120 (91.6%)) with only 11 studies (8.4%) from Upper Middle-Income Countries (n = 6), Lower Middle-Income Countries (n = 4) and a 'Lower Income' country (n=1). Figure 2 shows the value for percentage change in PED visits and number of days included in the study period. There is a suggestion that smaller study periods show a greater reduction; likely due to studies with shorter study periods focussing on the 'lockdown' period in their respective countries Conclusion: This systematic review demonstrates that pandemics have significantly different impacts on paediatric emergency service utilisation depending on the epidemic/pandemic. Evidence from 80 papers that across the world demonstrates children's attendances to Emergency Departments significantly fell during the COVID19 pandemic. The reasons for this are not entirely clear but are likely related to the public health response and parent/carer concern about the severity of the disease process. As public health messaging can impact on public behaviours, public health departments and related healthcare organisations must be aware how fear of viruses amongst the general public may influence their response to public health advice. There is inequality between low-middle and high income countries in reporting the impact of emergency service utilisation for children.